2009
DOI: 10.1261/rna.1650109
|View full text |Cite
|
Sign up to set email alerts
|

Activation of decapping involves binding of the mRNA and facilitation of the post-binding steps by the Lsm1-7–Pat1 complex

Abstract: Decapping is a critical step in the conserved 59-to-39 mRNA decay pathway of eukaryotes. The hetero-octameric Lsm1-7-Pat1 complex is required for normal rates of decapping in this pathway. This complex also protects the mRNA 39-ends from trimming in vivo. To elucidate the mechanism of decapping, we analyzed multiple lsm1 mutants, lsm1-6, lsm1-8, lsm1-9, and lsm1-14, all of which are defective in decapping and 39-end protection but unaffected in Lsm1-7-Pat1 complex integrity. The RNA binding ability of the muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 61 publications
5
39
0
Order By: Relevance
“…First, as expected and as we had observed previously with the wild-type complex (Chowdhury et al 2007;Chowdhury and Tharun 2009), a ∼23-kD band radiolabeled in a UV irradiation-dependent manner was clearly visible in crosslinking reactions carried out using both the complexes. This band has the expected mobility of Flag-Lsm1, and we have shown earlier via immunoprecipitation analyses that it does contain FlagLsm1 (Chowdhury et al 2007;Chowdhury and Tharun 2009). Second, in crosslinking reactions carried out using the wildtype complex, at least two more bands of lower mobility (∼65 kD and ∼97 kD) were also detectable in longer exposures, although one of them (∼97 kD) was weak.…”
Section: Pat1 Pat1δsupporting
confidence: 87%
See 2 more Smart Citations
“…First, as expected and as we had observed previously with the wild-type complex (Chowdhury et al 2007;Chowdhury and Tharun 2009), a ∼23-kD band radiolabeled in a UV irradiation-dependent manner was clearly visible in crosslinking reactions carried out using both the complexes. This band has the expected mobility of Flag-Lsm1, and we have shown earlier via immunoprecipitation analyses that it does contain FlagLsm1 (Chowdhury et al 2007;Chowdhury and Tharun 2009). Second, in crosslinking reactions carried out using the wildtype complex, at least two more bands of lower mobility (∼65 kD and ∼97 kD) were also detectable in longer exposures, although one of them (∼97 kD) was weak.…”
Section: Pat1 Pat1δsupporting
confidence: 87%
“…This may partly be to do with the smaller size of the Lsm1-7 complex compared with the wild-type Lsm1-7-Pat1 complex (∼97 kD vs. ∼185 kD). Second, while the Lsm1-7-Pat1 complex clearly exhibited a higher affinity for the PGK1-A 5 RNA than the PGK1 RNA as expected and as observed earlier (Chowdhury and Tharun 2009;Chowdhury et al 2012), such binding preference could not be observed with the Lsm1-7 complex. Very similar results were also observed when the experiments were carried out using the MFA2 and MFA2-A 5 RNAs (42-mer RNA derived from the 3 ′ UTR of MFA2 and the 3 ′ -penta-adenylated version of such RNA) as substrates for gel shift assays (Fig.…”
Section: Lsm1-7 Complex Assembles In Pat1δ Cellssupporting
confidence: 79%
See 1 more Smart Citation
“…complex (Chowdhury and Tharun 2009). An important role for Snf1 in the regulation of mRNA turnover has recently been uncovered in studies using conditional Snf1 kinase alleles (Young et al 2012;Braun et al 2014).…”
Section: -Deoxyglucose Resistance In Yeastmentioning
confidence: 99%
“…For example, in budding yeast, all mRNA decapping and 59-39 decay requires the general activator Dcp1, whereas bulk decay requires Dhh1 and the Pat1/Lsm1-7 complex, and nonsense mediated decay requires the Upf proteins (Beelman et al 1996;He et al 1997;Tharun et al 2000;Coller et al 2001;He and Jacobson 2001;Chowdhury and Tharun 2009). In Saccharomyces cerevisiae, the enhancer of decapping protein family (Edc1-3) activates decapping as part of an adaptive response to carbon source shifts or by promoting decay of specific transcripts (DeRisi et al 1997;Dunckley et al 2001;Schwartz et al 2003;Kshirsagar and Parker 2004;Badis et al 2004;Dong et al 2007).…”
Section: Introductionmentioning
confidence: 99%